Inaktivasi Termal Spora Jamur Eupenicillium Javanicum Dalam Jus Nanas - Adella, Lufya; Evelyn, Evelyn; Muria, Sri Rezeki (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Eupenicilium Javanicum is a mold that has high heat resistance. The purpose of this study was to determine the effect of temperature (T: 80 ° C, 85 ° C, 90 ° C) at soluble solid SS: 10 ° Brix on the thermal inactivation of E. Javanicum spores. Then determine the value of D and Z. This study uses the thermal method of pasteurization process and spore calculation using the spread plate method. The D-values obtained at SS 10 ° Brix for temperatures 80, 85 and 90 ° C were 10.82; 4.63; and 1.45 minutes and the Z-value obtained is in the at 11,47 ° C. It was shown that haiger temperature resulted in the decreasing of the timeneeded to inactivate the spores. The results of this study emphasize the importance of temperature to the D and Z value for pineapple juice pasteurization.Keywords: Ascospore, Inactivation, Pasteurization, Pineapple juice, E. Javanicum.